Prayer and the Transformation of Public Life in South Africa - Koopman, Nico (Interpretation, 2014)
This essay discusses the meaning of prayer, worship, and liturgy for the transformation and renewal of public life. As a crucial practice of the church, prayer creates, enhances, and nurtures a vision of a new society of holiness and justice. Prayer fosters courageous criticism of individuals and institutions where this vision is betrayed. Prayer thirdly forms and transforms humans into people of virtue and character who seek the good society through concrete obedience, quests for solidarity and justice, as well as practices of suffering and active and hopeful waiting upon God. I investigate the role that prayer played in the resistance against the apartheid regime, and spell out some implications of this threefold task of prayer for contemporary South Africa.